'Like Relatives Consoling Each Other After a Tragedy': Mourning, Vulnerability, and Hospitality in Justin Cartwright's White Lightning. Issue 2 (3rd July 2019) - Ateh Laue, Kharys
Abstract : This paper examines the ethical development of James Kronk's interracial and interspecies relationships in White Lightning, arguing that the process of mourning facilitates his empathetic shift in attitude towards the marginalized Other. Judith Butler's theory on grieving, as well as posthumanist scholarship, frames my contention that Kronk, by engaging in grief as an ethical resource, comes to recognize the vulnerability to death that he shares with those who are different from himself. This recognition of shared mortality, I argue, enables him to identify with Others and thereby leads him to a sense of moral responsibility for a Xhosa family and a baboon. Kronk's attempts at hospitality, however, do more harm than good. I read the collapse of his relationships, with both Daisy's family and Piet, through the lens of Jacques Derrida's notion of 'hostipitality', that is, the idea that hospitality and hostility are inextricably entangled. Ultimately, I conclude that those acts that Kronk initially believes to be hospitable later manifest in violence, resulting in the deaths of Zwelakhe and Piet, the very beings he had set out to protect.